Isolation, cloning and analysis of the hexose transporter 6 gene (HXT6) in a native strain of Saccharomyces cerevisiae IBRC-M30069 - Solmaz Azizi; Alireza Tarinejad; Mohammad Pazhang (Biological Journal of Microorganism, 2016)
Introduction: The Saccharomyces cerevisiae yeast is one of the most important microorganisms to produce ethanol. The S. cerevisiae has 20 genes that encode hexose transporter proteins. Among these gene families, seven genes HXT7-HXT1 have important an role in alcohol production. The researchers proved that alcohol fermentation goes up by increasing the expression of these genes which results in increasing ethanol production.